Critical Legal Studies: Civil Code in Philosophical Basis - Lia Salsiah (Budapest International Research and Critics University, 2022)
Civil Code which is a provision or regulation relating to someone personal with other people, or also civil law has a broad scope in its arrangement. One field of law that regulates the relationships between individuals in society with certain means. The classification of existing civil law includes: Family law; the law of wealth; material law; engagement laws; and inheritance law. A critical study of civil law that has been applied in Indonesia by using a normative juridical research method, so that should be the basis of his thinking is the philosophy of the Pancasila. The results of the discussion as it is known that Pancasila is the source of all sources of the Indonesian rule of law. This must be in accordance with the philosophy of Pancasila, which is the soul of the struggle of the nation's fighters, as a unifying tool, from the previously fragmented by a region, race, ethnicity, class, and religion.